Ensuring the security of synthetic biology—towards a 5P governance strategy - Kelle, Alexander (Springer Netherlands, 2009)
Over recent years the label “synthetic biology” has been attached to a number of diverse research and commercial activities, ranging from the search for a minimal cell to the quick delivery of customized genes by DNA synthesis companies. Based on the analysis of biosecurity issues surrounding synthetic biology during the SYNBIOSAFE project, this paper will first provide a rationale for taking security, in addition to safety aspects of this new field, seriously. It will then take stock of the initiatives and measures that have already been taken in this area and will lastly try to map out future areas of activities in order to minimise the security risks emanating from this promising new field of scientific inquiry and technological progress.